2011
DOI: 10.1021/am101055r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of Polythiophene:Fullerene Blends on Different Electrodes Using Near Edge X-ray Absorption Fine Structure

Abstract: We study the top surface composition of blends of the conjugated polymer regioregular poly-3-hexylthiophene (P3HT) with the fullerene (6,6)-phenyl-C(61)-butyric acid methyl ester (PCBM), an important model system for organic photovoltaics (OPVs), using near-edge X-ray absorption fine structure spectroscopy (NEXAFS). We compare the ratio of P3HT to PCBM near the air/film interface that results from preparing blend films on two sets of substrates: (1) poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 47 publications
7
37
0
Order By: Relevance
“…The vertical stratification can be controlled based on the modification of the surface energy of the substrate and the casting materials. Evidence shows that the modification of the substrate surface tends to affect the stratification in the interface or bulk region rather than at the top surface region . For example, DSIMS measurements of APFO‐3:PCBM blend films showed that, whilst the free surface is always enriched with the lower‐surface‐energy component APFO‐3, the composition profiles near the substrate interface can be changed by changing the substrate from silicon to gold .…”
Section: Surface Free Energymentioning
confidence: 99%
“…The vertical stratification can be controlled based on the modification of the surface energy of the substrate and the casting materials. Evidence shows that the modification of the substrate surface tends to affect the stratification in the interface or bulk region rather than at the top surface region . For example, DSIMS measurements of APFO‐3:PCBM blend films showed that, whilst the free surface is always enriched with the lower‐surface‐energy component APFO‐3, the composition profiles near the substrate interface can be changed by changing the substrate from silicon to gold .…”
Section: Surface Free Energymentioning
confidence: 99%
“…XANES may effectively identify various elements or the same element but in various chemical environment, which is very suitable for the characterization of the film composition . Actually, XANES has been widely applied to investigate the surface and interface composition in solar cells …”
Section: Carbon Nanostructures In Energy Applicationsmentioning
confidence: 99%
“…However, the enrichment of P3HT was found to modify with octyltrichlorosilane at the buried interface of SiO 2 with low surface energy . Another example showed the investigation of the top surface composition in blended P3HT and PCBM by using XANES . Tillack et al found the enrichment of P3HT at the top surface by XANES spectra and revealed that the substrate treatments didn't affect the enrichment, thus the changed performance by substrate treatments should be related to the substrate interface or the bulk of the film .…”
Section: Carbon Nanostructures In Energy Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been shown to be critical in understanding how some devices operate, as for example in section 4.2, where charge transport in the vicinity of the donor-acceptor heterojunction of an OPV had a more substantial effect on GR than did the meso-scale morphology. However, some features on the meso-scale are of interest, such as the presence of wetting layers [443] which accumulate at the electrodes OPVs [444][445][446][447][448], or the degree of mixing of the matrix and dye in an OLED [449]. Furthermore, although research has generally centred on what optical and electronic properties using a blend of OSCs can endow a device (e.g.…”
Section: Different Ways Of Defining Morphologymentioning
confidence: 99%